2005
DOI: 10.1177/106591290505800112
|View full text |Cite
|
Sign up to set email alerts
|

Presidents and the Economic Agenda

Abstract: The president’s ability to influence the national policy agenda is an important component of presidential power. Although some maintain that presidents are favorably situated to set agendas, others demonstrate that the president’s agenda-setting skills vary considerably by policy area. What is more, scholars have yet to examine the impact presidents have had focusing attention on the economy, an issue of vital importance to their political success. Extending previous research on presidential agenda setting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…In changing the salience of an issue, the media can aid in the prioritization process that leads to changes in what issues are considered on the formal agenda. Many studies have shown that media attention can set the agenda of policymaking institutions, such as Congress and the presidency (e.g., Baumgartner & Jones, 1993; Edwards & Wood, 1999; Eshbaugh‐Soha & Peake, 2005; Peake & Eshbaugh‐Soha, 2008). Others have demonstrated that the agenda‐setting effects of issue salience are conditioned by certain characteristics of issues, such as its obtrusiveness or previous levels of salience (Soroka, 2002; Walgrave & Van Aelst, 2006; Wood & Peake, 1998).…”
Section: Media Attention and Punctuated Equilibriummentioning
confidence: 99%
“…In changing the salience of an issue, the media can aid in the prioritization process that leads to changes in what issues are considered on the formal agenda. Many studies have shown that media attention can set the agenda of policymaking institutions, such as Congress and the presidency (e.g., Baumgartner & Jones, 1993; Edwards & Wood, 1999; Eshbaugh‐Soha & Peake, 2005; Peake & Eshbaugh‐Soha, 2008). Others have demonstrated that the agenda‐setting effects of issue salience are conditioned by certain characteristics of issues, such as its obtrusiveness or previous levels of salience (Soroka, 2002; Walgrave & Van Aelst, 2006; Wood & Peake, 1998).…”
Section: Media Attention and Punctuated Equilibriummentioning
confidence: 99%
“…For the most part, the findings illustrate a Congress that acts in isolation, unlikely to lead or follow at the agenda‐setting stage. Following the vector autoregression (VAR) techniques employed by Edwards and Wood (), Eshbaugh‐Soha and Peake () found the president's leadership of either congressional or media attention to economic policy to be limited. On the contrary, the findings suggest presidential responsiveness to both media and congressional attention to broad economic issues.…”
Section: Interinstitutional Agenda Influencementioning
confidence: 99%
“…The ability to influence the institutional policy agenda, those issues that receive considerable attention from decision makers, has long been considered one of the most important sources of political power (Anderson, ; Baumgartner & Jones, ; Cobb & Elder, ; Downs, ; Edwards & Wood, ; Flemming, Wood, & Bohte, ; Jones, ; Kingdon, ; Light, ; Peters & Hogwood, ; Walker, ), especially for the president (Bond & Fleischer, ; Edwards, ; Edwards & Barrett, ). Some recent theoretical development has occurred concerning this question, asserting the issue‐dependent nature of the relationships while questioning the president's leadership at the agenda stage (Edwards & Wood, ; Eshbaugh‐Soha & Peake, , ; Peake, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations